Effects of TGF-β3 on meniscus repair using human amniotic epithelial cells - Yupeng He; Ya Li; Xiaodong Zhi; Yuqiang Zhang; Wei Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Meniscus injury is one of the most common knee diseases, which is managed through conservative and surgical treatments. In recent years, biotherapy has shown great potential to treat various symptoms caused by meniscus injury repair. Human amniotic epithelial cells (hAECs), which are easy to acquire, non-tumorigenic, and high tri-lineage differentiation potential, are a promising cell source for biotherapy and tissue engineering applications. Studies have demonstrated that the Transforming Growth Factor-β3 (TGF-β3) can facilitate chondrocyte differentiation and maturation. Methods Both in vitro test and in vivo test were employed. In the in vitro test, human amniotic epithelial cells (hAECs), human amniotic mesenchymal stem cells (hAMCs), and fibrochondrocytes (FCs) were extracted and identified by flow cytometry and immunohistochemistry (IHC). These cells were treated with TGF-β3 for one week, followed by IHC staining and qPCR to explore TGF-β3-induced fibrocartilage formation in hAECs. In the in vivo tests, a meniscus injury model was established based on rabbits, and the Sham, the control (normal saline), and the hAECs + TGF-β3 groups were used. Additionally, the meniscus was collected and checked through general examination and IHC analysis 90 d after surgery. Results Routine transcriptome analysis confirmed that TGF-β3 induced the differentiation of amniotic epithelial cells (hAECs) into fibrochondrocytes through the Wnt signaling pathway. This finding was corroborated using Western blot (WB) and quantitative PCR (QPCR). Among the five experimental groups, the highest expression of target proteins and genes was detected in hAECs + TGF-β3 group, followed by the hAECs + hAMCs + TGF-β3 group, the hAMCs + TGF-β3 group, the hAECs + FCs group, and the FCs group. The observed differences were statistically significant (P < 0.05). In vivo, treatment with hAECs + TGF-β3 facilitated effective repair of damaged menisci. Conclusions hAECs + TGF-β3 can potentially promote the healing of meniscus injuries, laying the foundation for further research to promote its clinical translation. Trial registration Not applicable.